2020
DOI: 10.1002/ece3.7012
|View full text |Cite
|
Sign up to set email alerts
|

Centennial clonal stability of asexual Daphnia in Greenland lakes despite climate variability

Abstract: This is an open access article under the terms of the Creative Commons Attribution License, which permits use, distribution and reproduction in any medium, provided the original work is properly cited.

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
11
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
2

Relationship

2
4

Authors

Journals

citations
Cited by 7 publications
(14 citation statements)
references
References 76 publications
3
11
0
Order By: Relevance
“…Ephippia of Arctic, triploid populations of Daphnia pulicaria (asexually produced eggs) were collected in 2015 from sediment of two lakes in West Greenland (Kangerlussuaq area). Details on the lakes and sediment dating can be found in Dane et al (2020). Briefly, we sampled ephippia from sediment corresponding to several historical time periods in two lakes: Lake SS4 (Braya Sø): c .…”
Section: Methodsmentioning
confidence: 99%
“…Ephippia of Arctic, triploid populations of Daphnia pulicaria (asexually produced eggs) were collected in 2015 from sediment of two lakes in West Greenland (Kangerlussuaq area). Details on the lakes and sediment dating can be found in Dane et al (2020). Briefly, we sampled ephippia from sediment corresponding to several historical time periods in two lakes: Lake SS4 (Braya Sø): c .…”
Section: Methodsmentioning
confidence: 99%
“…We can extract DNA from these preserved diapausing eggs, and thereby reconstruct population genetic dynamics (Burge et al, 2018; Orsini et al, 2016). Although previous studies have revealed the evolutionary processes of Daphnia using diapausing eggs (e.g., Decaestecker et al, 2007; Hairston et al, 1999; Stoks et al, 2016), only three prior studies have observed long‐term genetic dynamics of Daphnia species including the early stage of colonisation (Conde‐Porcuna et al, 2021; Dane et al, 2020; Möst et al, 2015). Möst et al (2015) analysed 40 years of long‐term genetic dynamics of colonisation and establishment by Daphnia pulicaria that consisted of cyclic parthenogenetic lineages and possibly a few obligate parthenogenetic lineages.…”
Section: Introductionmentioning
confidence: 99%
“…Möst et al (2015) analysed 40 years of long‐term genetic dynamics of colonisation and establishment by Daphnia pulicaria that consisted of cyclic parthenogenetic lineages and possibly a few obligate parthenogenetic lineages. Dane et al (2020) and Conde‐Porcuna et al (2021) analysed long‐term genetic dynamics of an obligate parthenogenetic Daphnia pulex species complex. Dane et al (2020) observed the population genetic dynamics of obligate parthenogenetic D. pulicaria for three centuries including colonisation of three lakes in Greenland.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations